Hubungan Pelayanan Informasi Obat (PIO) Terhadap Kepuasan Pasien Instalasi Farmasi Klinik Griya Sehat Metro - Safira Silvia Revani; Afi Sania Rosanti; Mida Pratiwi; Diah Kartika Putri (Journal of Innovative and Creativity, 2025)
Drug information services are an important aspect of improving pharmaceutical services or raising public awareness of the pharmacist profession. By providing drug information services to patients, pharmacists can contribute to ensuring patients receive optimal therapy. The purpose of this study was to analyze the relationship between drug information services (PIO) and patient satisfaction at the Griya Sehat Metro Clinic pharmacy and to determine the level of patient satisfaction with drug information services at the Griya Sehat Metro Clinic. This study employed a quantitative method with a cross-sectional design and a sample size of 115 respondents. The instrument used in this study was a questionnaire with five dimensions of Servqual. Based on the results, there was a relationship between medication information services and patient satisfaction at the pharmacy department of Klinik Griya Sehat Metro, with a P-value of 0.000. The level of satisfaction with medication information services among patients at the pharmacy department of Klinik Griya Sehat Metro for medication information services was categorized as very good at 62,6%. Patient satisfaction for the reliability dimension was categorized as satisfied at 74,8%, the responsiveness dimension was categorized as satisfied at 63,5%, the assurance dimension was categorized as satisfied at 67,8%, the empathy dimension was categorized as satisfied at 69,6%, and the tangibility dimension was categorized as satisfied at 70,4%. The conclusion is that there is a relationship between medication information services and patient satisfaction at the pharmacy department of Klinik Griya Sehat Metro.